A high-strength cellulose acetate blended fiber fabric and dyeing process thereof

By grafting and polymerizing tris(β-ethylpiperazine) phosphate with cellulose acetate and blending it with polyacrylonitrile to form cellulose acetate blended fibers and their fabrics, the fracture strength of polyacrylonitrile fibers is solved. The problem of low and non-flame retardant properties achieves high strength and good flame retardant properties, and improves the dyeing effect.

CN118087082BActive Publication Date: 2025-02-18ZHEJIANG ALICE DYEING & FINISHING CO LTD

Patent Information

Application Number
CN202410221221.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-28
Publication Date
2025-02-18
Estimated Expiration
2044-02-28

AI Technical Summary

Technical Problem

Polyacrylonitrile fibers and their fabrics have problems with low breaking strength and no flame retardant properties.

Method used

By grafting and polymerizing the alkenyl-containing tris(β-ethylpiperazine) phosphate functional monomer with cellulose acetate, a polymer grafted cellulose acetate was obtained and then blended with polyacrylonitrile. Form cellulose acetate blended fibers and their fabrics.

Benefits of technology

The fracture strength and flame retardant properties of polyacrylonitrile fibers are improved. The ultimate oxygen index of fiber fabrics reaches 26.4-31.9%, which has good flame retardant properties and improves the dyeing rate and dyeing effect of dyes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004718257070000031
    Figure BDA0004718257070000031
  • Figure BDA0004718257070000032
    Figure BDA0004718257070000032
  • Figure BDA0004718257070000101
    Figure BDA0004718257070000101
Patent Text Reader

Abstract

The present invention relates to the field of cellulose technology, and discloses a high-strength cellulose acetate blended fiber fabric and a dyeing process thereof. The present invention grafts alkenyl-containing tris (β-maleic acid ethyl piperazine) phosphate and acrylonitrile with cellulose acetate under the initiation of ammonium persulfate to obtain polymer-grafted cellulose acetate, which is then blended with polyacrylonitrile to obtain cellulose acetate blended fiber and its fabric. After cellulose acetate is grafted with acrylonitrile monomer, the interface compatibility between cellulose acetate and polyacrylonitrile is better, and the rigid skeleton of cellulose acetate after spinning can improve the breaking strength and mechanical properties of polyacrylonitrile. The polymer grafted with cellulose acetate contains an expansion flame-retardant structure of piperazine phosphate, which can promote the formation of an expansion carbon layer in the fiber during combustion, improve the limiting oxygen index of the fiber fabric, and has good flame retardant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cellulose, in particular to a high-strength cellulose acetate blended fiber fabric and a dyeing process thereof. Background Art

[0002] Cellulose acetate is a chemically modified polymer compound obtained by esterifying the hydroxyl groups in cellulose molecules with acetic acid. It has low cost, good biocompatibility, high spinning and weaving performance, high strength, good elasticity, and is widely used in fiber fabrics and other fields. Blending cellulose acetate with silk, polyacrylonitrile fiber, polyester, etc. can produce composite fibers with excellent performance.

[0003] Polyacrylonitrile fiber is a common chemical synthetic fiber with a simple preparation method. It can be blended with wool, cotton, and rayon to form fiber fabrics. However, polyacrylonitrile fiber and its fabrics have defects such as poor strength and lack of flame retardancy, which hinder the development and application of polyacrylonitrile fiber. Patent No. CN10049160C discloses wet spinning of copolymerized polyacrylonitrile and cellulose acetate to obtain copolymerized polyacrylonitrile fiber with easy-to-control fiber water absorption and low preparation cost. However, the patent does not improve the strength and flame retardancy of polyacrylonitrile fiber. Summary of the invention

[0004] The invention provides a high-strength cellulose acetate blended fiber fabric and a dyeing process thereof, which solves the problems that acrylic fiber and its fabric have low breaking strength, no flame retardant property, poor dye uptake and poor dyeing effect.

[0005] The technical solution of the present invention is: a method for preparing a high-strength cellulose acetate blended fiber fabric:

[0006] S1. Add N,N-dimethylacetamide and cellulose acetate to a reaction bottle, heat to 70-80°C, stir and mix, then dropwise add ammonium persulfate aqueous solution, and then add the structural formula tris(β-ethylmaleate piperazine) phosphate and acrylonitrile, react for 6-12 hours, filter with suction, wash the filter cake with water and ethanol in turn, and obtain polymer-grafted cellulose acetate.

[0007] S2. Add N, N-dimethylacetamide, polyacrylonitrile and polymer-grafted cellulose acetate into a reaction bottle, stir and mix at 40-60°C for 6-12h to prepare a spinning solution, perform wet spinning, use a 40-50% N, N-dimethylacetamide aqueous solution as a coagulation bath to obtain primary fibers, and then stretch them to control the stretching multiple to 3-4 times, and shape them to obtain cellulose acetate blended fibers; then perform spinning, dyeing and weaving to obtain high-strength cellulose acetate blended fiber fabrics.

[0008] Furthermore, the ratio of N,N-dimethylacetamide, cellulose acetate, ammonium persulfate aqueous solution, tri(β-ethylmaleate piperazine) phosphate, and acrylonitrile in S1 is (10-15) mL: 1 g: (0.8-1) mL: (0.1-0.3) g: (0.15-0.4) g; the mass fraction of the ammonium persulfate aqueous solution is (3-8) mg / mL.

[0009] Furthermore, the ratio of N,N-dimethylacetamide, polyacrylonitrile, and polymer-grafted cellulose acetate in S2 is (5-6) mL: 1 g: (0.05-0.15) g.

[0010] Further, the dyeing process in S2 is: placing the cellulose acetate blended fiber in a dye solution containing a dye, controlling the bath ratio to be 1:(25-35), controlling the dyeing temperature to be 90-95°C, and dyeing time to be 40-60min; wherein the pH of the dye solution is 5-6, and the dye solution contains a dye with a mass concentration of 1.5-2.5g / L, 4-5g / L of sodium sulfate, and 0.7-1g / L of an anti-settling agent. Then, soap boiling is performed, the fiber is taken out, dried at 80-100°C for 10-20min, and baked at 150-170°C for 30-90s.

[0011] Further, the preparation method of tris(β-ethylmaleate piperazine) phosphate is as follows:

[0012] S1. Add acetone solvent, tert-butyl 4-(2-hydroxyethyl)piperazine-1-carboxylate, and maleic anhydride to a reaction flask equipped with a condenser reflux tube, heat to 50-55°C and react for 2-3 hours, concentrate to remove acetone, dissolve the product in dichloromethane, add trifluoroacetic acid, react at room temperature for 2-4 hours, concentrate to remove dichloromethane and trifluoroacetic acid, and recrystallize the product in ethanol aqueous solution to obtain ethyl piperazine maleate. The reaction formula is:

[0013]

[0014] S2, add methanol solvent, ethyl piperazine maleate, tris(β-chloroethyl) phosphate, and triethylamine to a reaction bottle equipped with a condenser reflux tube, heat to 60-65°C and react for 12-18h, concentrate to remove methanol after the reaction, and recrystallize the product in ethanol to obtain tris(β-ethyl piperazine maleate) phosphate. The reaction formula is:

[0015]

[0016] Furthermore, in the preparation method of tris(β-ethylpiperazinemaleate)phosphate, the ratio of acetone solvent, tert-butyl 4-(2-hydroxyethyl)piperazine-1-carboxylate, and maleic anhydride is (10-20) mL: 1 g: (0.46-0.52) g.

[0017] Furthermore, in the preparation method of tris(β-ethylpiperazine maleate) phosphate, the ratio of methanol solvent, ethylpiperazine maleate, tris(β-chloroethyl) phosphate and triethylamine is (40-60) mL: 1 g: (2-2.8) g: (1.1-1.3) g.

[0018] The technical effect of the present invention is that the alkenyl-containing tris(β-ethylpiperazine maleate) phosphate functional monomer and acrylonitrile are grafted and polymerized with cellulose acetate under the initiation of ammonium persulfate to obtain polymer-grafted cellulose acetate, which is then blended with polyacrylonitrile to obtain cellulose acetate blended fibers and fabrics thereof. After the cellulose acetate is grafted with acrylonitrile monomer, the interface compatibility between the cellulose acetate and the polyacrylonitrile is better, and the rigid skeleton of the cellulose acetate after spinning can improve the fracture strength and mechanical properties of the polyacrylonitrile.

[0019] The cellulose acetate grafted polymer of the present invention contains an expansion flame retardant structure of piperazine phosphate, which can promote the fiber to form an expansion carbon layer during combustion, improve the limiting oxygen index of the fiber fabric, and has good flame retardant performance.

[0020] The present invention grafts carboxyl-containing tris(β-ethylmaleate piperazine) phosphate, acrylonitrile and cellulose acetate to obtain polymer-grafted cellulose acetate, thereby introducing a large number of carboxyl groups into the cellulose acetate. After spinning with polyacrylonitrile, the fiber contains carboxyl groups to generate carboxyl anions, which can generate electrostatic interactions and hydrogen bonds with cations and other groups in dye molecules such as basic orange 21 and cationic brilliant red 5GN, so that the dye molecules can be better combined with the fiber fabric, thereby improving the dye uptake and dyeing effect of the dye. DETAILED DESCRIPTION

[0021] The specific implementation of the present invention is:

[0022] (1) Acetone solvent, tert-butyl 4-(2-hydroxyethyl)piperazine-1-carboxylate, and maleic anhydride in a ratio of (10-20) mL: 1 g: (0.46-0.52) g are added to a reaction flask equipped with a condenser reflux tube, the temperature is raised to 50-55° C. and the reaction is carried out for 2-3 hours. The acetone is concentrated to remove the product, and trifluoroacetic acid is added. The reaction is carried out at room temperature for 2-4 hours. The dichloromethane and trifluoroacetic acid are concentrated to remove the product, and the product is recrystallized in an ethanol aqueous solution to obtain ethyl piperazine maleate.

[0023] (2) Add methanol solvent, ethyl piperazine maleate, tri(β-chloroethyl) phosphate and triethylamine in a ratio of (40-60) mL: 1 g: (2-2.8) g: (1.1-1.3) g to a reaction flask equipped with a condenser reflux tube, heat to 60-65° C. and react for 12-18 hours. After the reaction, concentrate to remove methanol, and recrystallize the product in ethanol to obtain tri(β-ethyl piperazine maleate) phosphate.

[0024] (3) Add N,N-dimethylacetamide and cellulose acetate to a reaction bottle, heat to 70-80°C, stir and mix, then add ammonium persulfate aqueous solution dropwise, mix and add tris(β-ethylmaleate piperazine) phosphate and acrylonitrile, wherein the ratio of N,N-dimethylacetamide, cellulose acetate, ammonium persulfate aqueous solution, tris(β-ethylmaleate piperazine) phosphate and acrylonitrile is (10-15) mL: 1 g: (0.8-1) mL: (0.1-0.3) g: (0.15-0.4) g; the mass fraction of the ammonium persulfate aqueous solution is (3-8) mg / mL; react for 6-12 hours, filter, and wash the filter cake with water and ethanol in turn to obtain polymer-grafted cellulose acetate.

[0025] (4) Adding N,N-dimethylacetamide, polyacrylonitrile and polymer-grafted cellulose acetate in a ratio of (5-6) mL: 1 g: (0.05-0.15) g into a reaction bottle, stirring and mixing at 40-60° C. for 6-12 h to prepare a spinning solution, wet spinning, using a 40-50% N,N-dimethylacetamide aqueous solution as a coagulation bath to obtain nascent fibers, and then stretching, controlling the stretching multiple to 3-4 times, and shaping to obtain cellulose acetate blended fibers; then spinning, and then placing the cellulose acetate blended fibers in a dye solution containing a dye for dyeing, controlling the bath ratio to 1: (25-35), controlling the dyeing temperature to 90-95° C., and dyeing time to 40-60 min; wherein the pH of the dye solution is 5-6, and the dye solution contains a dye with a mass concentration of 1.5-2.5 g / L, 4-5 g / L of sodium sulfate, and 0.7-1 g / L of an anti-settling agent. Then, the soap is boiled, the fibers are taken out, dried at 80-100°C for 10-20 minutes, and baked at 150-170°C for 30-90 seconds. Finally, the fibers are woven to obtain high-strength cellulose acetate blended fiber fabrics.

[0026] Example 1

[0027] (1) 10 mL of acetone solvent, 0.5 g of tert-butyl 4-(2-hydroxyethyl)piperazine-1-carboxylate, and 0.23 g of maleic anhydride were added to a reaction flask equipped with a condenser reflux tube, the temperature was raised to 55° C. and the reaction was carried out for 2 h. The acetone was concentrated to remove the product, and 3.5 mL of trifluoroacetic acid was added to the product. The reaction was carried out at room temperature for 3 h. The dichloromethane and trifluoroacetic acid were concentrated to remove the product, and the product was recrystallized in an ethanol aqueous solution to obtain ethyl piperazine maleate.

[0028] (2) 25 mL of methanol solvent, 0.5 g of ethyl maleate piperazine, 1.2 g of tri(β-chloroethyl) phosphate, and 0.62 g of triethylamine were added to a reaction flask equipped with a condenser reflux tube, and the temperature was raised to 60° C. for reaction for 18 h. After the reaction, the methanol was concentrated to remove the methanol, and the product was recrystallized in ethanol to obtain tri(β-ethyl maleate piperazine) phosphate.

[0029] (3) 100 mL of N,N-dimethylacetamide and 10 g of cellulose acetate were added to a reaction bottle, heated to 75°C, stirred and mixed, and then 8 mL of 3 mg / mL ammonium persulfate aqueous solution was added dropwise. After mixing, 1 g of tris(β-ethylmaleate piperazine) phosphate and 1.5 g of acrylonitrile were added, and the reaction was carried out for 6 h. The filter cake was washed with water and ethanol in turn to obtain polymer-grafted cellulose acetate.

[0030] (4) 500 mL of N, N-dimethylacetamide, 100 g of polyacrylonitrile, and 5 g of polymer-grafted cellulose acetate were added to a reaction bottle, stirred and mixed at 40°C for 12 h to prepare a spinning solution, and wet spinning was performed. A 45% N, N-dimethylacetamide aqueous solution was used as a coagulation bath to obtain primary fibers, which were then stretched and the stretching multiple was controlled to be 3.8 times, and shaped to obtain cellulose acetate blended fibers; then spinning was performed, and the cellulose acetate blended fibers were placed in a dye solution with a pH of 5 for dyeing for 50 min, the bath ratio was controlled to be 1:30, the dyeing temperature was 95°C, and the dye solution contained a mass concentration of 2 g / L of basic orange 21, 5 g / L of sodium sulfate, and 0.7 g / L of anti-settling agent water-based polyamide wax S-321; then soap boiling was performed, the fibers were taken out, dried at 80°C for 20 min, and baked at 170°C for 3 s. Finally, weaving was performed to obtain high-strength cellulose acetate blended fiber fabrics.

[0031] Example 2

[0032] (1) 120 mL of N,N-dimethylacetamide and 10 g of cellulose acetate were added to a reaction bottle, heated to 80° C., stirred and mixed, and then 10 mL of a 4 mg / mL ammonium persulfate aqueous solution was added dropwise. After mixing, 1.6 g of tris(β-ethylpiperazinemaleate)phosphate (prepared in the same manner as in Example 1) and 2 g of acrylonitrile were added. The reaction was continued for 12 h, and the filter cake was washed with water and ethanol in turn to obtain polymer-grafted cellulose acetate.

[0033] (2) 550 mL of N, N-dimethylacetamide, 100 g of polyacrylonitrile, and 8 g of polymer-grafted cellulose acetate were added to a reaction bottle, stirred and mixed at 60°C for 6 h to prepare a spinning solution, and wet spinning was performed. A 50% N, N-dimethylacetamide aqueous solution was used as a coagulation bath to obtain primary fibers, which were then stretched and the stretching multiple was controlled to be 3.8 times, and shaped to obtain cellulose acetate blended fibers; then spinning was performed, and the cellulose acetate blended fibers were placed in a dye solution with a pH of 5 for dyeing for 50 min, the bath ratio was controlled to be 1:35, the dyeing temperature was 90°C, and the dye solution contained a mass concentration of 2 g / L of basic orange 21, 4.5 g / L of sodium sulfate, and 1 g / L of anti-settling agent water-based polyamide wax S-321; then soap boiling was performed, the fibers were taken out, dried at 90°C for 10 min, and baked at 150°C for 90 s. Finally, weaving was performed to obtain high-strength cellulose acetate blended fiber fabrics.

[0034] Example 3

[0035] (1) 150 mL of N,N-dimethylacetamide and 10 g of cellulose acetate were added to a reaction bottle, heated to 70° C., stirred and mixed, and then 10 mL of a 6 mg / mL ammonium persulfate aqueous solution was added dropwise. After mixing, 2.2 g of tris(β-ethylpiperazinemaleate)phosphate (prepared in the same manner as in Example 1) and 3.3 g of acrylonitrile were added. The reaction was continued for 12 h, and the filter cake was washed with water and ethanol in turn to obtain polymer-grafted cellulose acetate.

[0036] (2) 600 mL of N, N-dimethylacetamide, 100 g of polyacrylonitrile, and 12 g of polymer-grafted cellulose acetate were added to a reaction bottle, stirred and mixed at 40°C for 12 h to prepare a spinning solution, and wet spinning was performed. A 45% N, N-dimethylacetamide aqueous solution was used as a coagulation bath to obtain primary fibers, which were then stretched and the stretching multiple was controlled to be 3.8 times, and shaped to obtain cellulose acetate blended fibers; then spinning was performed, and the cellulose acetate blended fibers were placed in a dye solution with a pH of 5 for dyeing for 50 min, the bath ratio was controlled to be 1:35, the dyeing temperature was 95°C, and the dye solution contained a mass concentration of 2.5 g / L of cationic brilliant red 5GN, 4 g / L of sodium sulfate, and 0.7 g / L of anti-settling agent water-based polyamide wax S-321; then soap boiling was performed, the fibers were taken out, dried at 100°C for 10 min, and baked at 160°C for 60 s. Finally, weaving was performed to obtain high-strength cellulose acetate blended fiber fabrics.

[0037] Example 4

[0038] (1) 150 mL of N,N-dimethylacetamide and 10 g of cellulose acetate were added to a reaction bottle, heated to 70° C., stirred and mixed, and then 10 mL of an aqueous solution of ammonium persulfate having a mass fraction of 8 mg / mL was added dropwise. After mixing, 3 g of tris(β-ethylpiperazinemaleate)phosphate (prepared in the same manner as in Example 1) and 4 g of acrylonitrile were added. The reaction was continued for 12 h, and the mixture was filtered. The filter cake was washed with water and ethanol in turn to obtain polymer-grafted cellulose acetate.

[0039] (2) 600 mL of N, N-dimethylacetamide, 100 g of polyacrylonitrile, and 15 g of polymer-grafted cellulose acetate were added to a reaction bottle, stirred and mixed at 50°C for 12 h to prepare a spinning solution, and wet spinning was performed. A 40% N, N-dimethylacetamide aqueous solution was used as a coagulation bath to obtain primary fibers, which were then stretched and the stretching multiple was controlled to be 3.8 times, and shaped to obtain cellulose acetate blended fibers; then spinning was performed, and the cellulose acetate blended fibers were placed in a dye solution with a pH of 6 for dyeing for 50 min, the bath ratio was controlled to be 1:25, the dyeing temperature was 90°C, and the dye solution contained a mass concentration of 1.5 g / L of cationic brilliant red 5GN, 4 g / L of sodium sulfate, and 0.8 g / L of anti-settling agent water-based polyamide wax S-321; then soap boiling was performed, the fibers were taken out, dried at 80°C for 20 min, and baked at 150°C for 90 s. Finally, weaving was performed to obtain high-strength cellulose acetate blended fiber fabrics.

[0040] Comparative Example 1

[0041] (1) 500 mL of N, N-dimethylacetamide and 100 g of polyacrylonitrile were added to a reaction bottle, stirred and mixed at 40°C for 12 h to prepare a spinning solution, and wet spinning was performed. A 45% N, N-dimethylacetamide aqueous solution was used as a coagulation bath to obtain primary fibers, which were then stretched and shaped to obtain polyacrylonitrile fibers. The fibers were then spun and placed in a dye solution with a pH of 5 for dyeing for 50 min. The bath ratio was controlled to be 1:30 and the dyeing temperature was 95°C. The dye solution contained 2 g / L of basic orange 21, 5 g / L of sodium sulfate, and 0.7 g / L of anti-settling agent water-based polyamide wax S-321. The fibers were then soaped and taken out, dried at 80°C for 20 min, and baked at 170°C for 3 s. Finally, the fibers were woven to obtain fiber fabrics.

[0042] Comparative Example 2

[0043] 500mL N, N-dimethylacetamide, 100g polyacrylonitrile and 5g cellulose acetate were added to a reaction bottle, stirred and mixed at 40℃ for 12h to prepare a spinning solution, wet spinning was performed, and a 45% N, N-dimethylacetamide aqueous solution was used as a coagulation bath to obtain primary fibers, which were then stretched and the stretching multiple was controlled to be 3.8 times, and shaped to obtain cellulose acetate blended fibers; then spinning was performed, and the cellulose acetate blended fibers were placed in a dye solution with a pH of 5 for dyeing for 50min, the bath ratio was controlled to be 1:30, the dyeing temperature was 95℃, and the dye solution contained a mass concentration of 2g / L basic orange 21, 5g / L sodium sulfate, and 0.7g / L anti-settling agent water-based polyamide wax S-321; then soap boiling was performed, the fibers were taken out, dried at 80℃ for 20min, and baked at 170℃ for 3s. Finally, weaving was performed to obtain cellulose acetate blended fiber fabrics.

[0044] Comparative Example 3

[0045] (1) 100 mL of N,N-dimethylacetamide and 10 g of cellulose acetate were added to a reaction bottle, heated to 75° C., stirred and mixed, and then 8 mL of a 3 mg / mL ammonium persulfate aqueous solution was added dropwise. After mixing, 1 g of tris(β-ethylpiperazinemaleate)phosphate (prepared in the same manner as in Example 1) was added, reacted for 6 h, filtered, and the filter cake was washed with water and ethanol in turn to obtain polymer-grafted cellulose acetate.

[0046] (2) 500 mL of N, N-dimethylacetamide, 100 g of polyacrylonitrile, and 5 g of polymer-grafted cellulose acetate were added to a reaction bottle, stirred and mixed at 40°C for 12 h to prepare a spinning solution, and wet spinning was performed. A 45% N, N-dimethylacetamide aqueous solution was used as a coagulation bath to obtain primary fibers, which were then stretched at a stretching multiple of 3.8 times and shaped to obtain cellulose acetate blended fibers; spinning was then performed, and the cellulose acetate blended fibers were placed in a dye solution with a pH of 5 for dyeing for 50 min, with a bath ratio of 1:30 and a dyeing temperature of 95°C. The dye solution contained a mass concentration of 2 g / L of basic orange 21, 5 g / L of sodium sulfate, and 0.7 g / L of an anti-settling agent, water-based polyamide wax S-321; soap boiling was then performed, the fibers were taken out, dried at 80°C for 20 min, and baked at 170°C for 3 s. Finally, weaving was performed to obtain cellulose acetate blended fiber fabrics.

[0047] Comparative Example 4

[0048] (1) 100 mL of N,N-dimethylacetamide and 10 g of cellulose acetate were added to a reaction bottle, heated to 75°C, stirred and mixed, and then 8 mL of 3 mg / mL ammonium persulfate aqueous solution was added dropwise. After mixing, 1.5 g of acrylonitrile was added, reacted for 6 h, filtered, and the filter cake was washed with water and ethanol in turn to obtain polymer-grafted cellulose acetate.

[0049] (2) 500 mL of N, N-dimethylacetamide, 100 g of polyacrylonitrile, and 5 g of polymer-grafted cellulose acetate were added to a reaction bottle, stirred and mixed at 40°C for 12 h to prepare a spinning solution, and wet spinning was performed. A 45% N, N-dimethylacetamide aqueous solution was used as a coagulation bath to obtain primary fibers, which were then stretched and the stretching multiple was controlled to be 3.8 times, and shaped to obtain cellulose acetate blended fibers; then spinning was performed, and the cellulose acetate blended fibers were placed in a dye solution with a pH of 5 for dyeing for 50 min, the bath ratio was controlled to be 1:30, the dyeing temperature was 95°C, and the dye solution contained a mass concentration of 2 g / L of basic orange 21, 5 g / L of sodium sulfate, and 0.7 g / L of anti-settling agent water-based polyamide wax S-321; then soap boiling was performed, the fibers were taken out, dried at 80°C for 20 min, and baked at 170°C for 3 s. Finally, weaving was performed to obtain cellulose acetate blended fiber fabrics.

[0050] The linear density of the fibers prepared in each embodiment and comparative example is 1.67 dext, and the mechanical properties are tested by an electronic single fiber strength tester at a tensile rate of 20 mm / min. Each sample is measured 10 times and the average value is taken.

[0051] The flame retardant properties of the fiber fabrics prepared in the embodiments and comparative examples were tested using an oxygen index tester in accordance with GB / T 5454-1997.

[0052]

[0053] In each embodiment, ammonium persulfate is used as an initiator to graft and polymerize alkenyl-containing tris(β-ethylpiperazine maleate) phosphate, acrylonitrile and cellulose acetate to obtain polymer-grafted cellulose acetate, which is then blended with polyacrylonitrile to obtain cellulose acetate blended fibers and fabrics thereof. After cellulose acetate is grafted with acrylonitrile monomer, the interface compatibility between cellulose acetate and polyacrylonitrile is better, and the rigid skeleton of cellulose acetate after spinning can improve the breaking strength of polyacrylonitrile. At the same time, the polymer grafted with cellulose acetate contains an expanding flame-retardant structure of piperazine phosphate, which can promote the formation of an expanding carbon layer on the fiber during combustion, thereby improving the limiting oxygen index of the fiber fabric to 26.4-31.9%, and having excellent flame retardant properties.

[0054] Comparative Example 1 does not add polymer grafted cellulose acetate, the breaking strength of polyacrylonitrile fiber is low, and the limiting oxygen index is very low, and it does not have flame retardant properties. Comparative Example 2 spins polyacrylonitrile with ordinary cellulose acetate, and the interface compatibility between polyacrylonitrile and cellulose acetate is not good. After spinning, cellulose acetate will affect the mechanical properties of polyacrylonitrile and reduce the breaking strength. Comparative Example 3 uses tris (β-ethyl maleate piperazine) phosphate to graft polymerize with cellulose acetate, and the obtained polymer grafted cellulose acetate contains the expansion flame retardant structure of piperazine phosphate, which significantly improves the limiting oxygen index and flame retardant properties of the fiber fabric; however, during the graft polymerization, no acrylonitrile monomer is added, and the compatibility of the polymer grafted cellulose acetate with polyacrylonitrile is poor, and the breaking strength of the fiber is not well improved. Comparative Example 4 uses acrylonitrile monomer to graft polymerize with cellulose acetate, and the obtained polymer grafted cellulose acetate has good interface compatibility with polyacrylonitrile, which can improve the breaking strength of the fiber, but does not contain the expansion flame retardant structure of piperazine phosphate, and does not improve the limiting oxygen index and flame retardant properties of the fiber fabric.

[0055] Basic Orange 21 and Cationic Brilliant Red 5GN were respectively added to acetone solvent to prepare a dye solution with a concentration of 0-100 mg / L. The absorbance at the maximum absorption wavelength was measured using an ultraviolet-visible spectrophotometer to draw a standard absorbance curve.

[0056] The dye uptake rate was tested by residual liquid: the dye solution without adding the fiber was used as the blank group, 5 mL of the residual liquid after fiber dyeing was transferred into 20 mL of acetone solvent, and distilled water was added to make up the volume. The absorbance at the maximum absorption wavelength was measured by UV-visible spectrophotometer, and the concentration of the residual liquid was calculated according to the standard absorbance curve to calculate the dye uptake rate W. W = (C 0 -C 1 ) / C 0 ×100%. C0 is the blank dye solution; C1 The concentration of residual liquid after fiber dyeing.

[0057] Dyeing rate (%) Example 1 73.8 Example 2 76.4 Example 3 77.2 Example 4 74.0 Comparative Example 1 64.1 Comparative Example 2 65.2 Comparative Example 3 75.1 Comparative Example 4 63.9

[0058] In each embodiment, ammonium persulfate is used as an initiator to graft carboxyl-containing tris(β-ethylmaleate piperazine) phosphate, acrylonitrile and cellulose acetate to obtain polymer-grafted cellulose acetate, thereby introducing a large number of carboxyl groups into cellulose acetate. After spinning with polyacrylonitrile, the fiber contains carboxyl groups to produce carboxyl anions, which can electrostatically interact and hydrogen bond with cations and other groups in dye molecules such as basic orange 21 and cationic brilliant red 5GN, so that the dye molecules can be better combined with the fiber fabric, thereby improving the dyeing rate and dyeing effect of the dye.

Claims

1. A method for preparing a high-strength cellulose acetate blended fiber fabric, characterized in that: The preparation method is as follows: S1. Add N,N-dimethylacetamide and cellulose acetate to a reaction bottle, heat to 70-80°C, stir and mix, then dropwise add aqueous ammonium persulfate solution, mix and then add tris(β-ethylmaleate piperazine) phosphate and acrylonitrile, react for 6-12h, filter and wash to obtain polymer-grafted cellulose acetate; S2, adding N,N-dimethylacetamide, polyacrylonitrile, and polymer-grafted cellulose acetate into a reaction bottle, stirring and mixing to form a spinning solution, performing wet spinning, using an aqueous solution of N,N-dimethylacetamide as a coagulation bath to obtain primary fibers, and then stretching and shaping to obtain cellulose acetate blended fibers; then spinning, dyeing, and weaving to obtain high-strength cellulose acetate blended fiber fabrics; The ratio of N,N-dimethylacetamide, cellulose acetate, ammonium persulfate aqueous solution, tri(β-ethylmaleate piperazine) phosphate, and acrylonitrile in S1 is (10-15) mL: 1 g: (0.8-1) mL: (0.1-0.3) g: (0.15-0.4) g; the mass fraction of the ammonium persulfate aqueous solution is (3-8) mg / mL; The stirring temperature in S2 is 40-60°C and the time is 6-12h; The ratio of N,N-dimethylacetamide, polyacrylonitrile, and polymer-grafted cellulose acetate in S2 is (5-6) mL: 1 g: (0.05-0.15) g; The preparation method of the tris(β-ethylmaleate piperazine) phosphate is as follows: (1) Add acetone solvent, tert-butyl 4-(2-hydroxyethyl)piperazine-1-carboxylate and maleic anhydride to a reaction flask equipped with a condenser reflux tube, heat to 50-55°C and react for 2-3 hours. After concentration, dissolve the product in dichloromethane, add trifluoroacetic acid, and react at room temperature for 2-4 hours. After concentration, recrystallize the product to obtain ethyl piperazine maleate; (2) Add methanol solvent, ethyl piperazine maleate, tri(β-chloroethyl) phosphate and triethylamine into a reaction bottle equipped with a condenser reflux tube, heat to 60-65°C and react for 12-18 hours. After concentration, the product is recrystallized to obtain tri(β-ethyl piperazine maleate) phosphate; In the preparation method of tris(β-ethylpiperazine maleate) phosphate, the ratio of acetone, 4-(2-hydroxyethyl)piperazine-1-carboxylic acid tert-butyl ester and maleic anhydride is (10-20) mL: 1 g: (0.46-0.52) g; In the preparation method of tris(β-ethylpiperazine maleate) phosphate, the ratio of methanol, ethylpiperazine maleate, tris(β-chloroethyl) phosphate and triethylamine is (40-60) mL: 1 g: (2-2.8) g: (1.1-1.3) g.

2. The method for preparing the high-strength cellulose acetate blended fiber fabric according to claim 1, characterized in that: The concentration of the N,N-dimethylacetamide aqueous solution in S2 is 40-50%; the stretching multiple is 3-4 times.

3. The method for preparing the high-strength cellulose acetate blended fiber fabric according to claim 1, characterized in that: The dyeing process in S2 is as follows: placing the cellulose acetate blended fiber in a dye solution containing a dye, controlling the bath ratio to be 1:(25-35), controlling the dyeing temperature to be 90-95° C., and dyeing time to be 40-60 min; then performing soap boiling, taking out the fiber, drying at 80-100° C. for 10-20 min, and baking at 150-170° C. for 30-90 s.

4. The method for preparing the high-strength cellulose acetate blended fiber fabric according to claim 3, characterized in that: The pH value of the dye liquor is 5-6, and the dye liquor contains 1.5-2.5 g / L of dye, 4-5 g / L of sodium sulfate, and 0.7-1 g / L of anti-settling agent in a mass concentration.

Citation Information

Patent Citations

  • Preparation of modified polyacrylonitrile fibre

    CN101435119A

  • Fibres, filaments and yarns made from a mixture of cellulose acetate and a polymer

    GB821097A

Cited By

  • Cellulose acetate composite fiber, preparation method thereof and application of cellulose acetate composite fiber in yarn

    CN121295388A